Jenar: A New Music Creation | Jenar: Sebuah Musik Kreasi Baru - I Wayan Aditya Febriana; I Kt. Suteja (GHURNITA: Jurnal Seni Karawitan, 2022)
Tagetes flower is one among the flowers whose existences are preserved, particularly on Bali Island. It functions as an ornamental plant and Hinduism ceremonies and ritual items. The yellow color of Tagetes flowers represents the God Mahadewa, the ruler of the west, especially for Hindu people to prepare the offering. There are several meanings contained about the yellow color from Tagetes flower, both etymologically and philosophically. In old Javanese (Kawi), the yellow color is well-known as Jenar. Departing from the meaning of yellow color in Tagetes flower, a new percussion creation was created, entitled Jenar. The idea of this work was inspired by the importance of yellow color in Tagetes flower, implemented into a percussion creation by using Gamelan Gong Kebyar. This percussion creation uses a method proposed by Alma M. Hawkins, namely the exploration, the improvisation, and the forming. This creation of work concept guided by a Balinese concept of Tri Angga: kawitan, pengawak, pengecet, combined with conservative patterns that well-developed both through the song’s structure and the playing technique, with an arrangement of musical elements such as tone, rhythm, dynamics, melody, tempo, and harmony. This percussion creation occurs 10 minutes duration within 29 supports including the composer. Jenar percussion creation was perfomed at Natya Mandala stage, Institut Seni Indonesia (ISI) Denpasar.